Análise multitemporal da cobertura do solo no bairro Apeú - Castanhal - PA - SILVEIRA, Josiane Martins de Queiroz Xavier (2023)
Monitoring the dynamics of land use and land cover is fundamental for territorial planning, quality of life and control of environmental impacts. The objective was to make a multitemporal analysis of the soil cover of the Apeú neighborhood, Castanhal-PA in the years 1989, 1999, 2008, 2018 and 2021 through Remote Sensing techniques. Digital orbital images obtained by the TM sensor, bands 3, 4 and 5, from the Landsat-5 Satellite for the years 1989, 1999 and 2008, and images from the Landsat-8 Satellite, bands 6, 5 and 4, for the years from 2018 and 2021, which were submitted to supervised classification by maximum likelihood. Subsequently, a map was obtained with the following land use classes: Urban Area; Exposed Soil; Vegetation pothole; Regenerating Vegetation; Dense Vegetation and Clouds. In the period between 1999 and 2008 there was a growth of 29.1% in the urban area of the apeú neighborhood. In 2021, there was a considerable increase in the areas of exposed soil and a reduction in dense vegetation, indicating the need for planning and soil inspection in the neighborhood. Remote sensing using the Maximum Likelihood Mathematical Algorithm allowed the assessment of soil dynamics in Bairro do Apeú.